2016
DOI: 10.1155/2016/2093171
|View full text |Cite
|
Sign up to set email alerts
|

Microflora Disturbance during Progression of Glucose Intolerance and Effect of Sitagliptin: An Animal Study

Abstract: Background. Emerging evidences have shown a close interplay between obesity, diabetes, and intestinal flora disturbance. Dipeptidyl peptidase-4 inhibitor, exemplified by sitagliptin, is highly efficacious in treating type 2 diabetes (T2DM), yet little is known if sitagliptin exerts beneficial effects on microbiota associated with obesity and T2DM. We evaluated changes of gut microbiota following the induction of obesity and T2DM in a streptozotocin treated high fat/high carbohydrate fed (HF/HC-STZ) rat model a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
70
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(85 citation statements)
references
References 50 publications
12
70
0
3
Order By: Relevance
“…A similar gut microbiota structure has also been observed in patients with type 2 diabetes and metabolic syndrome [53]. The abundance of Tenericutes has been linked to obesity or type 2 diabetes-associated metabolic parameters [54,55]. Although the effects of reducing the F/B ratio did not appear to be directly related to the presence or absence of bacteriocin during gavage in our study, treatment with L. acidophilus JCM 1132 had a delayed reducing effect on the F/B ratio.…”
Section: Discussionsupporting
confidence: 79%
“…A similar gut microbiota structure has also been observed in patients with type 2 diabetes and metabolic syndrome [53]. The abundance of Tenericutes has been linked to obesity or type 2 diabetes-associated metabolic parameters [54,55]. Although the effects of reducing the F/B ratio did not appear to be directly related to the presence or absence of bacteriocin during gavage in our study, treatment with L. acidophilus JCM 1132 had a delayed reducing effect on the F/B ratio.…”
Section: Discussionsupporting
confidence: 79%
“…Similarly, some researches found that gut microbiota were substantially altered in STZ-induced type 2 diabetic rats [15,30].…”
Section: Diabetic Central Neuropathy Refers To Neuronal Damage and Brmentioning
confidence: 89%
“…However, Waget A et al [14] reported that sitagliptin could regulate glucose level by triggering the gut-brain axis other than local inhibition of intestinal DPP-4 activity. Furthermore, sitagliptin treatment substantially changed the structure of gut microbiota in STZ-induced type 2 diabetic rats [15]. Additionally, recent studies have shown that sitagliptin could improve cognitive function in type 2 diabetic patients with and without Alzheimer's disease [16] and in insulin-resistant rats [17].…”
Section: (Dpp-4)mentioning
confidence: 99%
“…It has been found that Sitagliptin and Vildagliptin, DPP-4 inhibitors, altered gut microbial composition in diabetic rats. 58,59 These drugs reduced the diversity of microbiota, increased the abundances of SCFA-producing bacteria including Blautia, Roseburia, Clostridium, Baceroides, and Erysipelotrichaeae in gut microbiota and corrected the Bacteroidetes/Firmicutes ratio. 58,59 Therefore, it has been suggested that these drugs may have beneficial effects on blood glucose partly through maintaining the gut barrier integrity and correcting the dysbiosis of intestinal microbiota in diabetes, although human studies are needed in this regard.…”
Section: Other Drugs Proven To Benefit T2dmentioning
confidence: 99%